ZeOxaNMulti Trial: A Randomized, Double-Blinded, Placebo-Controlled Trial of Oral PMA-Zeolite to Prevent Chemotherapy-Induced Side Effects, in Particular, Peripheral Neuropathy - Vitale, Maria Giuseppa; Barbato, Carmela; Crispo, Anna; Habetswallner, Francesco; De Martino, Bernardo Maria; Riccardi, Ferdinando; Maione, Angela; Eisenwagen, Sandra; Vitale, Giovanna; Cartenì, Giacomo (Molecules (Basel, Switzerland), 2020)
Chemotherapy-induced peripheral neuropathy (CIPN) is the most frequently reported adverse effect of oxaliplatin. In this study, we set out to evaluate the role of the panaceo-micro-activation (PMA) zeolite in the reduction of the incidence of CIPN and hematological and liver toxicity. The possible impact of the PMA-zeolite as an adjuvant therapeutic agent is based on its detoxification properties toward agents promoting the development of neuropathy (e.g., ammonium—recognized as a neurotoxic agent produced by tumors), as well as its positive impact on immunity and oxidative stress through its effects in the gastrointestinal tract. From April 2015 to October 2018, a total of 120 patients (pts) diagnosed with predominantly colorectal cancer requiring oxaliplatin-based chemotherapy were randomized to receive either the PMA-zeolite (Multizeo Med) or placebo while undergoing oxaliplatin-based chemotherapy. A nerve-conduction study (NCS) was planned at the baseline, after three and six months of chemotherapy, to evaluate CIPN. Furthermore, the evaluation of hematological and liver toxicity was performed during every cycle of chemotherapy. 70.6% and 64.3% of patients developed CIPN in the placebo and the PMA-zeolite group, respectively. Patients treated with the PMA-zeolite were able to undergo more cycles of chemotherapy (p = 0.03), which also indicates a significant improvement in tolerance to the therapy. The group treated with the PMA-zeolite showed a lower CIPN (although not statistically significant within the whole group of subjects) compared to patients receiving placebo. This advantage was, however, statistically significant in men (p = 0.047). In addition, supplementation with the PMA-zeolite resulted in a lower incidence of severe-grade hematological toxicity (trend toward statistical significance of p = 0.09 was observed). Cancer patients may benefit from the therapy with the appropriate certified zeolite-products (e.g., the PMA-zeolite) for human use in CIPN. The lower CIPN (statistically significant results in the male subgroup) was accompanied by a trend of lower incidence of severe-grade hematological toxicity. Furthermore, these benefits led to a better tolerance toward chemotherapy (increase in cycles) and allow an improved compliance with the oncological treatment protocol.